Update on microbiota-derived therapies for recurrent Clostridioides difficile infections - Benech, Nicolas; Barbut, Frédéric; Fitzpatrick, Fidelma; Krutova, Marcela; Davies, Kerrie; Druart, Celine; Cordaillat-Simmons, Magali; Heritage, John; Guery, Benoît; Kuijper, Ed; ESGCD and ESGHAMI (Clinical microbiology and infection, 2024)
BACKGROUND: Faecal microbiota transplantation (FMT) is the standard treatment for patients with multiple recurrent Clostridioides difficile infection (rCDI). Recently, new commercially developed human microbiota-derived medicinal products have been evaluated and Food and Drug Administration-approved with considerable differences in terms of composition, administration, and targeted populations. OBJECTIVES: To review available data on the different microbiota-derived treatments at the stage of advanced clinical evaluation and research in rCDI in comparison with FMT. SOURCES: Phase II or III trials evaluating a microbiota-derived medicinal product to prevent rCDI. CONTENT: Two commercial microbiota-derived medicinal products are approved by the Food and Drug Administration: Rebyota (RBX2660 Ferring Pharmaceuticals, marketed in the United States) and VOWST (SER-109 -Seres Therapeutics, marketed in the United States), whereas VE303 (Vedanta Biosciences Inc) will be studied in phase III trial. RBX2660 and SER-109 are based on the processing of stools from healthy donors, whereas VE303 consists of a defined bacterial consortium originating from human stools and produced from clonal cell banks. All have proven efficacy to prevent rCDI compared with placebo in patients considered at high risk of recurrence. However, the heterogeneity of the inclusion criteria, and the time between each episode and CDI diagnostics makes direct comparison between trials difficult. The differences regarding the risk of recurrence between the treatment and placebo arms were lower than previously described for FMT (FMT: Δ = 50.5%; RBX2660-phase III: Δ = 13.1%; SER-109-phase III: Δ = 28%; high-dose VE303-phase-II: Δ = 31.7%). All treatments presented a good overall safety profile with mainly mild gastrointestinal symptoms. IMPLICATIONS: Stool-derived products and bacterial consortia need to be clearly distinguished in terms of product characterization and their associated risks with specific long-term post-marketing evaluation similar to registries used for FMT. Their place in the therapeutic strategy for patients with rCDI requires further studies to determine the most appropriate patient population and administration route to prevent rCDI.
Keywords: výsledek terapie; mikrobiota; Faecal microbiota transplantation; Clostridioides difficile; Treatment Outcome; klostridiové infekce; Humans; Recurrence; Clostridioides difficile infection; Recurrent Clostridioides difficile infection; Fecal Microbiota Transplantation; recidiva; Clostridium Infections; fekální transplantace; Microbiota; Microbiota-derived therapy; lidé; Live biotherapeutic products